FROM CLASSROOM TO CLOUD: UNVEILING THE DYNAMICS OF DIGITAL EDUCATION - Bilal Ahmad Rather (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This research article titled "From Classroom to Cloud: Unveiling the Dynamics of Digital Education" delves into the transformative journey of education in the digital age. The study systematically explores the paradigm shift from traditional classrooms to cloud-based platforms, examining the profound impact on pedagogical methodologies, student engagement, and overall learning experiences. Focusing on the integration of diverse digital technologies within cloud-based frameworks, the research illuminates the roles of learning management systems, virtual classrooms, collaborative tools, and emerging technologies. Additionally, it scrutinizes the evolution of pedagogical strategies, emphasizing educators' adaptation to the digital landscape and assessing the efficacy of interactive and collaborative approaches. The study also investigates the student-centric nature of cloud-based learning, addressing personalized educational experiences and inclusivity. By delving into challenges and opportunities associated with this transition, the research provides valuable insights for educators, policymakers, and stakeholders navigating the complexities of digital education.